Executive Functioning and School Performance Among Pediatric Survivors of Complex Congenital Heart Disease - Gerstle, Melissa (J Pediatr, 2016)
OBJECTIVE: To investigate the presence and severity of real-world impairments in executive functioning– responsible for children’s regulatory skills (metacognition, behavioral regulation) – and its potential impact on school performance among pediatric survivors of complex congenital heart disease (CHD). STUDY DESIGN: Survivors of complex CHD aged 8–16 years (n=143)and their parents/guardians from a regional CHD survivor registry participated (81% participation rate). Parents completed proxy measures of executive functioning, school competency, and school-related quality of life (QOL). Patients also completed a measure of school QOL and underwent IQ testing. Patients were categorized into two groups based on heart lesion complexity: two-ventricle or single-ventricle. RESULTS: Survivors of complex CHD performed significantly worse than norms for executive functioning, IQ, school competency, and school QOL. Metacognition was more severely affected than behavioral regulation, and metacognitive deficits were more often present in older children. Even after taking into account demographic factors, disease severity, and IQ, metacognition uniquely and strongly predicted poorer school performance. In exploratory analyses, patients with single-ventricle lesions were rated as having lower school competency and school QOL, and patients with two-ventricle lesions were rated as having poorer behavioral regulation. CONCLUSIONS: Survivors of complex CHD experience greater executive functioning difficulties than healthy peers, with metacognition particularly impacted and particularly relevant for day-to-day school performance. Especially in older children, clinicians should watch for metacognitive deficits, such as problems with organization, planning, self-monitoring, and follow-through on tasks.